Promoting Communication Through the English Day: An Experience After Studying an In-Service Course - Vega Mercedes (Profile: Issues in Teachers' Professional Development)
One of the main concerns I shared with other English teachers while taking an in-service course at the Universidad Nacional was that of providing opportunities for students to practice the language. Despite the difficulties (large classes, limited time for language teaching, and lack of student motivation, among others), we try to generate interactions that allow them to experiment with the language. Nonetheless, those practices are not enough. In this paper I describe the way an extracurricular activity was organized and carried out as a means to engage students in a meaningful activity: The English Day.